Peningkatan Keterampilan Menulis Narasi Siswa Kelas VII C SMP Negeri 1 Padang melalui Media Gambar Berseri - Wismi Lusita (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
This study aimed to describe the process of improving the year 7 students’ skill in writing narratives at class VII C of “SMP Negeri I Padang” by using serial pictures. The data of this study were the result of the observation on the actions of teachers in teaching process, students’ activities in learning, learning materials, and result of the narrative test. The data were collected by observation and testing techniques. The data obtained from the observations were analyzed qualitatively by using Schiedel model. Data in the form of the test results were analyzed quantitatively by using descriptive statistics and inferential statistics. The results of this study show that the use of serial pictures can improve students’ narrative writing skills.Kata-kata Kunci:menulis narasi, media gambar berseri, pembelajaran